2022
DOI: 10.3390/toxins14100650
|View full text |Cite
|
Sign up to set email alerts
|

Improved Analytical Approach for Determination of Tropane Alkaloids in Leafy Vegetables Based on µ-QuEChERS Combined with HPLC-MS/MS

Abstract: This work presents an optimized methodology based on the miniaturization of the original QuEChERS (μ-QuEChERS) followed by liquid chromatography coupled to mass spectrometry (HPLC-MS/MS) for the determination of tropane alkaloids (TAs), atropine, and scopolamine in leafy vegetable samples. The analytical methodology was successfully validated, demonstrating quantitation limits (MQL) ≤2.3 ng/g, good accuracy, and precision, with recoveries between 90–100% and RSD ≤ 13% for both analytes. The method was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Most of the studies determine the presence of atropine and scopolamine, or together with pyrrolizidine alkaloids. Moreover, other recently developed methods focus on the determination of TAs in cereals [31,32,38] and leafy vegetables [39].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies determine the presence of atropine and scopolamine, or together with pyrrolizidine alkaloids. Moreover, other recently developed methods focus on the determination of TAs in cereals [31,32,38] and leafy vegetables [39].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, QuEChERS was tested and introduced as the sample preparation protocol for other LC-MS/MS methods as well [ 16 , 17 , 18 ]. Recently published papers and standards describe QuEChERS employed in the analysis of mycotoxins, ergot alkaloid or Alternaria toxin [ 19 , 20 , 21 , 22 , 23 ]. Although the extraction of Alternaria toxins from food is preferably done with a methanolic medium, QuEChERS can successfully be applied for their extraction in various food samples as well [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The population is exposed to these natural toxins through food, usually of plant origin, although some studies have reported the transfer of TAs to animal foods, such as honey and milk [ 3 , 8 ]. Cereals and pseudocereals are the most contaminated foods [ 11 , 12 , 13 , 14 , 15 ], followed by teas, herbal teas [ 16 , 17 , 18 , 19 , 20 ], spices [ 21 ], honey [ 22 , 23 ], and vegetables [ 24 , 25 ]. Furthermore, over the past few years, the European Rapid Alert System for the Food and Feed (RASFF) portal has reported numerous alerts on different foodstuffs contaminated by TA-producing plants, such as Atropa belladonna , Datura stramonium , Mandragora , Hyoscyamus niger , and Solanum nigrum [ 3 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of this potential contamination and good manufacturing practices will reduce the risk of mixing toxic and non-toxic plants [ 3 ]. However, recently, another route of contamination was proposed [ 25 ]. This route involves horizontal transfer through the soil, which has already been proposed for other families of alkaloids, such as pyrrolizidine alkaloids (PAs) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%